Kriging-Based Timoshenko Beam Element for Static and Free Vibration Analyses - Wong F.T.; Syamsoeyadi H. (Institute of Research and Community Outreach - Petra Christian University, 2011)
An enhancement of the finite element method using Kriging interpolation (K-FEM) has been recently proposed and applied to solve one- and two- dimensional linear elasticity problems. The key advantage of this innovative method is that the polynomial refinement can be performed without adding nodes or changing the element connectivity. This paper presents the development of the K-FEM for static and free vibration analyses of Timoshenko beams. The transverse displacement and the rotation of the beam are independently approximated using Kriging interpolation. For each element, the interpolation function is constructed from a set of nodes within a prescribed domain of influence comprising the element and its several layers of neighbouring elements. In an attempt to eliminate the shear locking, the selective-reduced integration technique is utilized. The developed beam element is tested to several static and free vibration problems. The results demonstrate the excellent performance of the developed element.